PENGARUH MOTIVASI TERHADAP KINERJA APARATUR DI KANTOR CAMAT KERITANG KABUPATEN INDRAGIRI HILIR - Azhar Abbas (Dialektika Publik, 2019)
This study aims to determine the effect of Motivation on the performance of the apparatus in the Keritang Sub-district office, Indragiri Hilir district downstream. that the level of motivation of the apparatus in the office of Keritang Sub-District of Indragiri Hilir Regency is included in the high category. Furthermore, in the apparatus performance category at the Keritang Sub-District Office, Indragiri Hilir Regency is in a very high category, this might be caused by not doing the best if not coupled with good performance from the employees themselves, so therefore the awareness of the employees themselves on the importance of good performance can have an influence on service to the community. Hypothesis testing concludes that there is a negative and significant influence between motivation and performance. This is indicated by the test of the effect of the independent variable of motivation on performance variables which shows t count of 5.097 greater than the t table of 1.703 at the level of trust α = 0.05 and t table of 2.473 at the level of confidence α = 0.01. This shows that the alternative hypothesis (H1) is accepted, namely there is a significant effect between the independent variable motivation (X) on the dependent variable performance (Y).